Securing Databases: A Comparative Study on the Impact of Implementing SSL on MySQL 8.0.33 - Antoni Haikal; Heru Wijanarko; Ocha Oktafia; Muhammad Hikmah Husnuzon; Gunawan Gunawan; Hamdani Arif (Politeknik Negeri Malang, 2023)
The increasing reliance on online communication and data storage has made protecting sensitive information a top priority for businesses and individuals. This study investigates the effectiveness of different security protocols in safeguarding databases from external threats. By comparing the performance of databases that use SSL and those that do not, this project provided valuable insights into the importance of securing data in transit and the impact of security protocols on database performance. The results of this research could be helpful for companies and individuals looking to improve the security of their databases and protect sensitive information. These research findings demonstrate that enabling SSL encryption leads to longer average execution times for database operations. This latency can be attributed to the computational workload associated with SSL's encryption and decryption processes. However, the trade-off between performance and security is essential to safeguarding data in transit.